Los Angeles Dodgers 5 vs Atlanta Braves 2 at Dodger Stadium - Watkins, Howard::::::::: (1987)
Dodgers pitching coach in conference at mound; #9, #3 Steve Sax, #10 ?Anderson, #33 ?, and #57 Sean Hillegas walking back to dugout; umpire signaling for right handed reliever Viewed from centerfield